Mendelian randomization studies of lifestyle-related risk factors for stroke: a systematic review and meta-analysis - Tian, Yi; Tang, Xin; Liu, Yi; Liu, Shu Yi (Frontiers in Endocrinology, 2024)
Objective: Stroke risk factors often exert long-term effects, and Mendelian randomization (MR) offers significant advantages over traditional observational studies in evaluating the causal impact of these factors on stroke. This study aims to consolidate and evaluate the relationships between potential causal factors and stroke risk, drawing upon existing MR research.Methods: A comprehensive search for MR studies related to stroke was conducted up to August 2023 using databases such as PubMed, Web of Science, Embase, and Scopus. This meta-analysis examines the relationships between potential causative factors and stroke risk. Both random-effects and fixed-effects models were utilized to compile the dominance ratios of various causative elements linked to stroke. The reliability of the included studies was assessed according to the Strengthening the Reporting of Observational Studies in Epidemiology incorporating Mendelian Randomization (STROBE-MR) guidelines.The analysis identified several risk factors for stroke, including obesity, hypertension, lowdensity lipoprotein cholesterol (LDL-C), chronic kidney disease (CKD), and smoking. Protective factors included high-density lipoprotein cholesterol (HDL-C), estimated glomerular filtration rate (eGFR), and educational attainment. Subgroup analysis revealed that type 2 diabetes mellitus (T2DM), diastolic blood pressure (DBP) are risk factors for ischemic stroke (IS).This study confirms that variables such as obesity, hypertension, elevated LDL-C levels, CKD, and smoking are significantly linked to the development of stroke. Our findings provide new insights into genetic susceptibility and potential biological pathways involved in stroke development.